Mapping quantative trait loci controlling resistance to gastrointestinal nematode infections in mice. - Menge, D.M. (Jomo Kenyatta University of Agriculture and Technology, 2004)
Gastrointestinal nematodes are arguably the most important disease restricting domestic ruminant production. Control rests heavily on chemotherapy but resistance to anthelmintic drugs by the parasites poses a major threat to livestock industries worldwide. An alternative is to produce through selective breeding or genetic modification stock with enhanced resistance to infection. Rodent infections provide valuable models to analyse factors controlling resistance to economically important gastrointestinal nematode parasites. It has been shown that resistance and susceptibility in mice are genetically determined making it possible to identify genetic markers and then look for homologues in target ruminants or humans. This thesis reports mapping of quantitative trait loci (QTL) for resistance to Helgmosomides polygyrus (H polygyrus) in mice, a strongyloid worm whose biology is similar to the trichostrongyloid nematodes of economic importance in domestic ruminants. An F2 intercross of SWR and CBA strains that are resistant and susceptible to H polygyrus was used as resource population to map chromosomal regions associated with resistance. A total population of 520 F2, 120 SWR and 120 CBA mice were infected with H polygyrus given weekly for six weeks. Resistance phenotypes measured were a three-time point faecal egg count at week 2, 4 and 6, total worm count and granuloma score on intestinal mucosa at necropsy, immunoglobulin E and G 1 titres and mucosal mast cell proteases 1. A least square analysis ofvarriance showed a significant variation for all traits in both the pure lines and F2 intercross. A genome-wide quantitative trait locus (QTL) mapping was undertaken to evaluate the genetic basis of variation in the resistance traits in the F2 cross by selective DNA pooling and selective genotyping of individuals based on total worm count and an average of total worm count and the three time point faecal egg count. Analysis of selective DNA pools revealed QTL on chromosome 1, 13, 17 and 19 associated with total worm count which were also confirmed by selective genotyping for individual DNA samples hence showing the potential utility of this approach in QTL detection. Interval mapping (1M) analysis using maximum likelihood and least square methods detected 31 significant QTL affecting at least one of the resistance associated traits. Considering the relative positions and direction of additive and dominance effects of the detected QTLs, and taking the concept of pleiotropy into account, it can be envisaged that this experiment has detected 18 loci on 14 chromosomes controlling resistance to H. polygyrus infection in mice. A number of candidate genes for nematode infection resistance can be identified based on the QTL locations. Among the more interesting candidates are those that influence T cell responses, pro-inflammatory and other cytokines or particular components of the inflammatory response, the MHC region, supporting earlier work indicating the involvement of MHC-linked genes in resistance to H. polygyrus, mast cell proteases 1 and IgE production. However, the relative importance of these individual genes, and' others mapping to the identified QTL, remains to be determined although it is possible to see an overall role in regulating inflammatory responses, T cell and antibody responses and factors controlling the functionally important mast cell response. High resolution mapping of the detected QTL is going on using FdF7 advanced intercross lines (AIL) approach and the QTL on chromosome 1 and 17 have been confirmed and fine mapped to 5 cM in preparation for positional cloning upon further dissection of the QTL. This may lead to identification of the homologous genes in domestic ruminants through comparative mapping and as well provide valuable insights into the molecular basis of host resistance to GI nematodes, which will have important implications for the development of novel disease control strategies in man and livestock.